Oxygen vacancies on the surface of HxWO3−y for enhanced charge storage. Issue 16 (5th April 2018) - Wang, Haiyan; Fan, Ruxue; Miao, Jingyu; Chen, Jiayi; Mao, Shanjun; Deng, Jiang; Wang, Yong
Abstract : The dominant role of surface oxygen vacancies (OVs) in improving energy storage is underscored by comparing the OV-mediated charge storage performance of surface and bulk defective H x WO3− y with that of WO3 and bulk defective e-H x WO3− y . Abstract : The dominant role of surface oxygen vacancies (OVs) in improving energy storage is underscored by comparing the OV-mediated charge storage performance of surface and bulk defective H x WO3− y with that of WO3 and bulk defective e-H x WO3− y . It shows that surface OVs are key hot spots for faradaic reactions in H x WO3− y, which promotes the formation of certain W 5+ and W 4+ during the reduction process.